Knowledge sharing behaviour in the public sector: The business process management perspectives - Ismail, Noor Azizi; King, Malcolm (2004)

(untitled)
This Study focused on measuring the alignment of AIS requirement and AIS capacity among SMEs in Malaysia and then investigated the link between AIS aligment and performance.Using a mail questionnaire,data from 310 firms was collected on nineteen accounting information characteristics so that AIS requirement and AIS capacity could be compared.The results indicated that a significant proportion of Malaysian SMEs had achieved high AIS alignment.Furthermore,the group of SMEs with high AIS alignment had achieved better organisational performance than firm with low AIS alignment.The findings provided evidence of the importance of AIS alignment and deepened current understanding of the requirements for accounting information and the use of IT as an information processing mechanism.More importantly,it opens up possibilities for further study of AIS alignment in SMEs,both in Malaysia and on a global basis.